Violence and Violence Research in Africa South of the Sahara - Veit, Alex; Barolsky, Vanessa; Pillay, Suren (International Journal of Conflict and Violence (IJCV), 2011)
This review presents the major lines of investigation regarding violence in Africa since the Cold War. After a historical introduction to the development of violent phenomena and their political contexts, diverse issues such as civil war, democratization, vigilantism, and the role of youth are assessed. It is argued that recent research has produced important insights by re-focusing on violent phenomena beyond the state. Yet despite the increasing number of non-state violent actors active on the African continent, to speak of a “privatization” of violence may be premature.